Technology Integration in English Language Teaching: A SAMR-Based Analysis of Lecturers’ Practices in Higher Education - RIZKIYAH, FAIQOTUR (Journal of Language Teaching Lingustics and Literature, 2025)
This study investigates how English lecturers integrate Information and Communication Technology (ICT) into their teaching practices using the SAMR (Substitution, Augmentation, Modification, Redefinition) framework. A qualitative case study was conducted at a private university in Banyuwangi involving six English lecturers. Data were collected through classroom observations and semi-structured interviews and analyzed using the interactive model of Miles and Huberman. The findings show that technology integration occurred at all four SAMR levels. At the substitution level, lecturers mainly used PowerPoint as a presentation medium, maintaining teacher-centered instruction. At the augmentation level, lecturers utilized online dictionaries, search engines, grammar-checking tools, and plagiarism detectors to improve instructional efficiency. At the modification level, collaborative writing, peer feedback, and video-based speaking activities reshaped classroom interaction. At the redefinition level, students created multimodal digital projects and communicated with authentic audiences through online platforms. Overall, technology shifted learning from lecturer-centered delivery toward interactive, collaborative, and authentic English language learning.